Clinical, developmental and molecular update on Cornelia de Lange syndrome and the cohesin complex: Abstracts from the 2014 Scientific and Educational Symposium. (21st April 2015) - Kline, Antonie D.; Calof, Anne L.; Lander, Arthur D.; Gerton, Jennifer L.; Krantz, Ian D.; Dorsett, Dale; Deardorff, Matthew A.; Blagowidow, Natalie; Yokomori, Kyoko; Shirahige, Katsuhiko; Santos, Rosaysela; Woodman, Julie; et al.
Abstract: Cornelia de Lange Syndrome (CdLS) is the most common example of disorders of the cohesin complex, or cohesinopathies. There are a myriad of clinical issues facing individuals with CdLS, particularly in the neurodevelopmental system, which also have implications for the parents and caretakers, involved professionals, therapists, and schools. Basic research in developmental and cell biology on cohesin is showing significant progress, with improved understanding of the mechanisms and the possibility of potential therapeutics. The following abstracts are presentations from the 6th Cornelia de Lange Syndrome Scientific and Educational Symposium, which took place on June 25–26, 2014, in conjunction with the Cornelia de Lange Syndrome Foundation National Meeting in Costa Mesa, CA. The Research Committee of the CdLS Foundation organizes the meeting, reviews and accepts abstracts, and subsequently disseminates the information to the families through members of the Clinical Advisory Board. In addition to the scientific and clinical discussions, there were educationally focused talks related to practical aspects of behavior and development. AMA CME credits were provided by Greater Baltimore Medical Center, Baltimore, MD. © 2015 Wiley Periodicals, Inc.